Facile Surfactant‐, Reductant‐, and Ag Salt‐free Growth of Ag Nanoparticles with Controllable Size from 35 to 660 nm on Bulk Ag Materials. Issue 16 (18th June 2021) - Ou, Weihui; Shen, Junda; Lyu, Fucong; Xiao, Xufen; Zhou, Binbin; Lu, Jian; Li, Yang Yang
Abstract: Morphologically and dimensionally controlled growth of Ag nanocrystals has long been plagued by surfactants or capping agents that complicate downstream applications, unstable Ag salts that impaired the reproducibility, and multistep seed injection that is troublesome and time‐consuming. Here, we report a one‐pot electro‐chemical method to fast (∼2 min) produce Ag nanoparticles from commercial bulk Ag materials in a nitric acid solution, eliminating any need for surfactants or capping agents. Their size can be easily manipulated in an unprecedentedly wide range from 35 to 660 nm. Furthermore, the Ag nanoparticles are directly grown on the Ag substrate, highly desirable for promising applications such as catalysis and plasmonics. The mechanistic studies reveal that the concentration of Ag + in the diffusion layer nearby the surface, controlled by the magnitude and duration of voltage, is critical in governing the nanoparticle formation (<1.3 mM) and its dimensional adjustability. Abstract : A convenient and facile electrochemical method for growing Ag nanoparticles with tunable size from 35 to 660 nm on commercial bulk Ag material was developed. The Ag + concentration in the diffusion layer, easily controlled by the electrochemical parameters, plays a salient role in dimensional tunability of thus‐obtained Ag nanoparticles.